2017
DOI: 10.1159/000485452
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of MiR-136-5p Targeting NF-κB/A20 in the IL-17-Mediated Inflammatory Response after Spinal Cord Injury

Abstract: Background/Aims: The pathophysiology of spinal cord injury (SCI) results in serious damage to the human body via an increase in the secondary biological processes imposed by activated astrocytes. Abnormal expression of microRNAs after SCI has become a potential research focus. However, the underlying mechanisms are poorly understood. Methods: SCI models were established in rats using Allen’s method, and the BBB scoring method was employed to assess locomotor function. Lentivirus was used to infect rat astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 35 publications
(30 reference statements)
0
27
0
Order By: Relevance
“…Moreover, the functional relevance of miR-136 in vascular endothelial cell apoptosis has been previously demonstrated, and the activities of vascular endothelial cells are clearly associated with cardiovascular diseases [15]. He et al [16] have found that miR-136-5p may act as a significant molecule for the modulation of spinal cord injury lesions in rat models and may be useful for treating this disease. Another study has suggested that expression of miR-136-3p was elevated at 6 h after human chorionic gonadotropin administration in rat ovaries and rat granulosa cells [17].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the functional relevance of miR-136 in vascular endothelial cell apoptosis has been previously demonstrated, and the activities of vascular endothelial cells are clearly associated with cardiovascular diseases [15]. He et al [16] have found that miR-136-5p may act as a significant molecule for the modulation of spinal cord injury lesions in rat models and may be useful for treating this disease. Another study has suggested that expression of miR-136-3p was elevated at 6 h after human chorionic gonadotropin administration in rat ovaries and rat granulosa cells [17].…”
Section: Introductionmentioning
confidence: 96%
“…IL‐25 is an NF‐κB signaling pathway activator participating in multiple physiological processes of tumor cell, such as proliferation, apoptosis, and metastasis . Therefore, we supposed that IL‐25 mediates MVP expression by activating NF‐κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…IL-25 is an NF-κB signaling pathway activator participating in multiple physiological processes of tumor cell, such as proliferation, apoptosis, and metastasis. 32,33 Therefore, we supposed that IL-25 mediates MVP expression by activating NF-κB signaling pathway. To confirm our hypothesis, we detected the expression of NF-κB signaling pathway-associated proteins by western blot in IL-25 overexpressed and silenced cells.…”
Section: Il-25-induced Mvp Elevation In Lung Cancer Cells Requires mentioning
confidence: 99%
“…The recent increment in SCI cases could be attributed to a steady increase in vehicular accidents and falls (Chen et al, ). Traumatic SCI contributes to dyskinesia, chronic central pain, and subsequently intricate treatment (He et al, ). Secondary SCI, such as autophagy and apoptosis, could damage neighboring neurons that are not destroyed during the primary SCI, dramatically impacting the motor function recovery process (Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%